Semiotic Study: The Meaning Of Women In The Structure Of Social Political Movements In The 4 Series Of Books The Buru Island Tetralogy - Moh. Dey Prayogo (Berumpun: International Journal of Social, Politics, and Humanities, 2022)
This study tries to observe and describe the meaning of women in the socio-political movement in the colonial era, which was described by the writer Pramoedya Ananta Toer in the book tetralogy of Buru Island (Bumi Manusia, Anak Semua Bangsa, Jejak Langkah, and Rumah Kaca). The analysis in this study observes the three female characters described in the book as representations of the meaning of women, described by Pramoedya Ananta Toer as struggle figures in initiating socio-political movements. The book, which describes the embryonic formation of the Indonesian nation during colonialism, has the style and analogy of an emancipatory struggle in a society that does not look at gender, as well as the absence of previous research that holistically discusses the four series of books in the context of women and the socio-political movement as a whole. This study uses a qualitative approach using a semiotic analysis model from Charles Sanders Peirce, which includes representation, object, and interpretant, which is then supported by compatible literature studies. The results of research on women from the natural side or in terms of their strength to fight colonialism with socio-political movements are arranged in a network of text symbols in the Tetralogi Pulau Buru novel series.